RELATIONSHIP BETWEEN JOB STRESS AND NURSE PERFORMANCE AT ABDUL MANAP JAMBI HOSPITAL IN 2022 - Darmawanto, Darmawanto; Mawarti, Indah; Rudini, Dini (Program Studi Keperawatan Universitas Jambi, 2024)
A nurse is someone who works in a hospital and plays an important role in the delivery of health services. The performance of nurses issomething that can be felt by patients, if poor performance it can have animpact on decreasing the quality of service. Job stress has a negative impact on performance, because stress becomes an adaptive response that is channeled by individual differences or psychological processes, which are a consequence of any actions from outside the situation, or events that impose excessive psychological or physical exertion on a person.This study uses survey method research with an explanatory research approach or explanatory research to explain the relationship between two or more variables, namely